2022
DOI: 10.1111/jfpp.17174
|View full text |Cite
|
Sign up to set email alerts
|

Single and combined use of isomalt, polydextrose, and inulin as sugar substitutes in production of pectin jelly

Abstract: In this study, 60% of the total sugar (sucrose and corn syrup) in pectin jellies was substituted by using single or various combinations of the bulking agents: isomalt, polydextrose, and inulin. Substitution with isomalt resulted in lower hardness and flexibility and lower moisture content; it ended up with an opaque and rough appearance on the outer surface, thus causing lower sensory acceptability and shorter storage stability than conventional product. Substitution of sugars with inulin was found to be succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Moreover, Jiamjariyatam [ 44 ] showed that the toughness and hardness of GCs were significantly decreased by the incorporation of 20, 30, 40, 50, and 100% isomaltulose. Similarly, Ünal and Arslan [ 45 ] reported lower hardness, flexibility, and moisture content for isomaltitol-containing GCs than conventional sugar-containing samples. However, the substitution of sugars with isomaltitol negatively affected the sensory acceptability of GCs due to their opaque appearance.…”
Section: Preparation Of Gcs Based On Novel Formulationsmentioning
confidence: 92%
“…Moreover, Jiamjariyatam [ 44 ] showed that the toughness and hardness of GCs were significantly decreased by the incorporation of 20, 30, 40, 50, and 100% isomaltulose. Similarly, Ünal and Arslan [ 45 ] reported lower hardness, flexibility, and moisture content for isomaltitol-containing GCs than conventional sugar-containing samples. However, the substitution of sugars with isomaltitol negatively affected the sensory acceptability of GCs due to their opaque appearance.…”
Section: Preparation Of Gcs Based On Novel Formulationsmentioning
confidence: 92%
“…On the other hand, it is worth mentioning that when the crunchy texture is required for the product (as in the case of balah el sham and luqmat el qady), the panelists preferred the texture of these products when sugar syrup was used compared to those with sugarfree syrups (Table 4). Polydextrose stimulates desserts in preservation their creaminess and adds smoothness, suitable texture, and mouthfeel (Jana et al, 1994;Ünal, & Arslan, 2022). Ansari et al (2021) demonstrated, inulin and polydextrose, or resistant starch can be added to products as a prebiotic component to improve sensory characteristics with extending the product shelf life.…”
Section: Sensory Evaluation Of Dessert Products With Sugar Free Syrupsmentioning
confidence: 99%
“…Several studies have used prebiotics and polyols to substitute sugar in confectionery products [13][14][15][16][17]. However, from most of the literature found, there has been no research that combines the use of prebiotics and polyols to substitute sugar in jelly candy.…”
Section: Introductionmentioning
confidence: 99%